Avaliação genotóxica de esteróides anabolizantes sintéticos com uso do teste de micronúcleo em medula óssea de camundongos (Mus musculus) - Meireles, José Roberto Cardoso (2012)
The use of anabolic androgenic steroids (AAS) aiming the rapid development of muscle mass has increased in several populations worldwide. In spite the potential benefits of these drugs in treating some diseases their indiscriminate use can cause damage to health, such as alterations in cardiovascular and liver functions. Data from literature are controversial in relation to the association between AAS use and cancer development. Considering that cancer is a genetic disease, resulting from alterations in genes involved with the cellular proliferation and differentiation, or in genes compromised with DNA repair and apoptosis, this study aimed to evaluate the genotoxic potential of three ASS: deca-durabolin®, deposteron® and durateston® using the micronucleus test in bone marrow of rodents. Swiss male mice six to eight weeks of age were treated, by intramuscular injection, with each drug at three different concentrations: clinical dose (DC), clinical dose concentrated five times (5X DC) and concentrated ten times the clinical dose (DC 10X). One group of animals was treated with cyclophosphamide as a positive control (CP) and another group (negative control) with corn oil (CN). Animals were sacrificed 24h, 48h and 72h after treatment and immediately bone marrow was removed, processed and prepared smears on slides for microscopy. Micronuclei were computed in 1000 polychromatic erythrocytes for assessment of chromosomal damage. Cytotoxicity was assessed by determining the ratio PCE-NCE (erythrocyte normochromatic) in 200 erythrocytes/animal. The occurrence of micronuclei was significantly higher in the animals treated with drugs at higher concentration (DC 10X) compared to the other groups, except for the positive control. Moreover, the drugs in this concentration also induced cell cycle delay revealing cytotoxic effects. These results indicate that AAS induces, in mice, chromosomal damage and cytotoxicity in concentration dependence.